Evaluation of acetone-water separation in a packing column (Research, Society and Development, 2021)
In the present n the present work, the operation of a filling tower with glass rings in the process of acetone absorption by water is evaluated. The study is based on experimental data of Pressure Drop and concentration levels collected at the outlet of the device. Influences of operating parameters and geometry are evaluated using the ANOVA method and empirical models for both outlet concentrations and pressure drop are also presented.